КӨРКЕМ ӘДЕБИЯТЫМЫЗДА ӘДЕПЛИЛИК ҮЛГИЛЕРИ - Утегенова, Ж.Ж. (FAN va JAMIYAT, 2017)
The article is devoted to the description of the national values and the best gualities of the Karakalpak people that have been kept since ancient time: kindness, humanity, fried ship and love to Mother land on the material of extracts from the works of fiction.